1989
DOI: 10.1007/bf01739744
|View full text |Cite
|
Sign up to set email alerts
|

Visual search, EEG, and psychopathology in schizophrenic patients

Abstract: Twenty acutely admitted schizophrenic inpatients diagnosed according to RDC and 8 normal controls were instructed to search for a randomly located target letter (Z) in ten lists of 284 distractor letters of either rounded or angular shape projected on a screen (23 degrees x 15 degrees). Eye movements were recorded using infrared corneal reflection-pupil centre measurement. Search performance was defined as the search time in seconds from onset of the display until localization of the target. The EEG was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…These variables can be obtained by directly monitoring eye movements during visual search tasks using corneal reflection-pupil center instruments. Gaebel (1989) used this eye monitoring methodology and found that individuals with schizophrenia and nonpsychiatric controls did not differ significantly with regard to the number and path of directly monitored overt scan moves. Although the nature of the relationship between covert scanning of iconic images and overt scanning of visual displays is currently controversial (e.g., Klein, 1980), Gaebel’s (1989) results are consistent with the present finding that schizophrenic and nonpsychiatric individuals used a similar number and path of scan moves to search visual letter arrays.…”
Section: Discussionmentioning
confidence: 99%
“…These variables can be obtained by directly monitoring eye movements during visual search tasks using corneal reflection-pupil center instruments. Gaebel (1989) used this eye monitoring methodology and found that individuals with schizophrenia and nonpsychiatric controls did not differ significantly with regard to the number and path of directly monitored overt scan moves. Although the nature of the relationship between covert scanning of iconic images and overt scanning of visual displays is currently controversial (e.g., Klein, 1980), Gaebel’s (1989) results are consistent with the present finding that schizophrenic and nonpsychiatric individuals used a similar number and path of scan moves to search visual letter arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Schwierigkeit kann umgangen werden, wenn von den Pupillenrändern auf die Pupillen elektronisch hochgerechnet wird. Dieses äußerst präzise und artefaktarme Verfahren (KaI:: et al, 1987) hat jedoch in der Untersuchung von schizophrenlm Patienten bisher, aufgrund des vergleichsweise hohen technischen Aufwandes, nur in jüngster Zeit experimentelle Anwendung gefunden (Gaebel et al, 1986(Gaebel et al, . 1989Mosel' ct al., 1990;Amlt et al, 1993a, b).…”
Section: Meßtechnikunclassified